Tylenchids nematodes (Tylenchida) parasitizing field population of Harmonia axyridis, and Cycloneda sanguinea (Coleoptera, Coccinellidae) in Argentina - Camino, Nora B. (2016)
For the first time in Argentina, we report that in Harmonia axyridis Pallas, 1773, and Cycloneda sanguinea (Linnaeus, 1763) (Coleoptera, Coccinellidae) parasitizing by nematodes which belong to the family of Allantonematidae (Nematoda, Tylenchida). The genera are Metaparasitylenchus Wachek, 1955 (Nickle, 1967), Sulphuretylenchus Rühm, 1956 (Nickle, 1967) and Contortylenchus Rühm, 1956. They will be described and photographied afterwards.